2001
DOI: 10.4315/0362-028x-64.11.1841
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Petrifilm Plate Method for the Enumeration of Aerobic Microorganisms and Coliforms in Retailed Meat Samples

Abstract: This study was designed to compare the effectiveness and applicability of the Petrifilm plate method with the Association of Official Analytical Chemists' (AOAC) standard aerobic count method and violet red bile agar method for meat products. The comparison was carried out using 303 meat samples collected from various retailers: 110 pork samples, 87 chicken samples, and 107 beef samples. In the comparison of the correlation coefficient (R) between the conventional method and the Petrifilm plate method by a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 16 publications
0
11
0
4
Order By: Relevance
“…Alguns países como estados Unidos, Canadá, Austrália, Coréia, Portugal, Noruega, itália, entre outros, desenvolveram trabalhos e estudos colaborativos para avaliar a eficiência das placas Petrifilm e de outros métodos rápidos em relação aos métodos convencionais [6,7,8,11,16,19,23,24,29].…”
Section: -Introduçãounclassified
“…Alguns países como estados Unidos, Canadá, Austrália, Coréia, Portugal, Noruega, itália, entre outros, desenvolveram trabalhos e estudos colaborativos para avaliar a eficiência das placas Petrifilm e de outros métodos rápidos em relação aos métodos convencionais [6,7,8,11,16,19,23,24,29].…”
Section: -Introduçãounclassified
“…TAPC with Petrifilm plates is one of the most widely used methods for evaluating the cleanliness of food and production processes in the food processing industry (22,32), and TEPC with Petrifilm plates is a simple method for evaluating the most important 19). The results of all three methods were correlated, and TBL was a significant predictor of both TAPC and TEPC.…”
Section: Discussionmentioning
confidence: 99%
“…TM plates have been extensively tested and compared with several other counting methods, including the conventional pour plate method, and the results of these comparisons lead to the conclusion that Petrifilm TM AC plates are an excellent alternative to the conventional procedure for enumeration of microorganisms in foods, including milk and dairy products (4,5,7,9,10,12,13,16,18,19,24). Simplate TM plates have also been submitted to equivalence studies and good correlation indexes were also reported (3,11,15,22,29,30).…”
Section: Resultsmentioning
confidence: 99%